Opening Up: Clients’ Inner Struggles in the Initial Phase of Therapy - Kleiven, Gøril Solberg; Hjeltnes, Aslak; Råbu, Marit; Moltu, Christian (Frontiers in Psychology, 2020)
Objective: To explore how clients in clinical settings experience the process of opening up and sharing their inner experiences in the initial phase of therapy. Methods: Two psychotherapy sessions of clients (N = 11) were videotaped and followed by interviews. Interpersonal process recall was used to obtain in-depth descriptions of clients’ immediate experiences in session. A follow-up interview was conducted three months later. The interviews were analyzed using thematic analysis. Results: The data revealed how and why clients distanced themselves from inner experiences in the initial phase of therapy. The overarching theme was “Holding back and struggling to open up,” which included four subthemes: (a) fearing the intensity and consequences of negative emotions; (b) experiences of being incapable and bodily stuck; (c) being insecure about one’s worthiness and right to share inner experiences with the therapist; and (d) struggling with feeling disloyal to loved ones. Conclusions: The participants held back because they feared different consequences of opening up. A range of concerns led participants to distance themselves from their inner experiences and/or to refrain from openly talking about them to the therapist. Concerns related to appropriate interpersonal conduct as client were especially important. This knowledge is highly relevant to clinicians when building safety for psychotherapeutic work.